Dynamics of Muslim Minority Religion in East Amanuban District, South Central Timor Regency - Syamsudin, Kinkin (LP2M IAIN Palopo, 2025)
This article examines the religious dynamics of minority Muslim communities in East Amanuban District, South Central Timor Regency, East Nusa Tenggara Province. Despite living in a predominantly Protestant Christian community, the region's Muslim community is able to maintain its religious identity while contributing to the local social and cultural diversity. This study aims to: (1) outline the history of the entry of Islam in East Amanuban, (2) identify the strengths and weaknesses of the Muslim community, and (3) analyze the patterns of their social interaction with the non-Muslim majority community. Using a qualitative descriptive approach through field observations, interviews, and document studies, the study found that the main strength of the Muslim community lies in the relatively large number of mosques and the commitment of the community in preserving the teachings of Islam. The challenges faced include limited human resources, inadequate religious facilities, and the influence of local customs that sometimes contradict Islamic practices. On the other hand, the value of tolerance, social solidarity, and local cultural wisdom is an important capital for the sustainability of their Islamic identity. The results of this study emphasized the importance of strengthening religious institutions and cross-community cooperation to strengthen religious harmony in multicultural areas such as East Amandaban. Keywords: East Amanuban, interfaith tolerance, Muslimminority, religiosity, social dynamics